The Role of Transformative Projects in European Union Integration Dynamics - Kaveshnikov Nikolay Yu. (Современная Европа)
This paper introduces a new approach to understanding the deepening of integration. It examines how and under what conditions the implementation of large projects drives integration dynamics. The study begins by analyzing the demand and supply logic that underlies the explanatory integration theories, primarily two grand theories – neofunctionalism and liberal intergovernmentalism. Both theories agree that the demand for integration is crucial but differ on the nature of interest groups (purely national vs. national and transnational), the levels at which these groups demand integration (only national vs. national and transnational), and the role of supranational institutions. Both theories acknowledge the key role of member state governments at the polity level. Neofunctionalism and institutionalism recognize the role of governments at the level of politics as well, at least when studying significant reforms of specific EU policies. National policymakers are usually ready to deliver the supply of integration (political decisions) when these decisions provide them sufficient compensation for any loss of their autonomy, usually in the form of additional pubic or elite support. What characteristics should a new integration project have in order to accumulate the demand, push politicians to deliver the supply, and be able to trigger the systemic transformation of regional integration organizations like the EU? The study proposes the concept of a transformative project – a type of integration project that can significantly impact integration dynamics and entail systemic changes in governance, polity, and degree of policy coordination. Based on an analysis of the EU’s history, we outline the key characteristics of a transformative project, including complexity to induce a spillover effect, a practice-oriented nature combined with long-term political goals, broad support among stakeholders and society, tangible benefits that impact daily life to promote socialization, a solid groundwork (experience with regulation at the supranational level), and linkage to a global context. The author concludes with several assumptions about the potential of the EU Green Deal as a transformative project.